2019
DOI: 10.4274/jpr.galenos.2018.30075
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Platelet Parameters and Neutrophil/Lymphocyte Ratios in Children with Acute Rheumatic Fever

Abstract: Acute rheumatic fever (ARF) is an inflammatory disease resulting from an autoimmune response to group A beta haemolytic streptococcal infection in sensitive individuals. It is particularly important due to being capable of leading to rheumatic heart disease associated with high morbidity and mortality (1-4). Cytokines produced by lymphocytes and macrophages that are differentiated following an antigenic stimulus play an important role in the triggering of immunological and inflammatory reactions and therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…Platelets are increased by IL-6 stimulation. 1,9,12 Unfortunately, in our study, there was no statistically significant correlation between platelet-to-lymphocyte ratio and severity of carditis. Ozdemir et al showed higher platelet levels in children with rheumatic fever compared with healthy children.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…Platelets are increased by IL-6 stimulation. 1,9,12 Unfortunately, in our study, there was no statistically significant correlation between platelet-to-lymphocyte ratio and severity of carditis. Ozdemir et al showed higher platelet levels in children with rheumatic fever compared with healthy children.…”
Section: Discussioncontrasting
confidence: 81%
“…Rheumatic heart disease is the most common form of paediatric heart disease in the world and is the leading cause of cardiac death in the first five decades of life. 9 Mitral regurgitation ranging from mild to severe was present in 95%, mitral stenosis in 16%, aortic regurgitation in 44% and tricuspid regurgitation in 56% of the patients in our study. More subjects had severe carditis with a combination of mitral regurgitation and aortic regurgitation.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…[29] In a study conducted by Aşık et al, in which 50 patients with ARF and 50 control groups participated, a statistically significant difference was found, with WBC, neutrophil count, neutrophil/lymphocyte count ratio, and platelet high in the case group, while lymphocyte, hemoglobin, and MPV were high in the control group. [30] In the literature, SII and L/CRP has not yet been studied in patients with ARF. In our study, when the laboratory values of the patients were examined, it was determined that WBC, PLT, MPV, NE, PCT, MCHC, MO, CRP, ESH, NLR, NMO, TLO, EO, and SII values decreased significantly after treatment, while MCH, RDW, PDW, L/CRP values increased significantly after treatment.…”
Section: Discussionmentioning
confidence: 99%